1994
DOI: 10.1007/bf00203500
|View full text |Cite
|
Sign up to set email alerts
|

Cystosarcoma phyllodes of the prostate: MRI findings

Abstract: Cystosarcoma phyllodes of the prostate is a rare, relatively benign sarcoma of the prostate. We describe the magnetic resonance imaging findings in an unusual case of cystosarcoma phyllodes which resulted in extensive local recurrence and sarcomatous degeneration. Although uncommon, radiologists should be aware of the existence of cystosarcoma phyllodes of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
7
0
2
Order By: Relevance
“…Thirty‐six cases of phyllodes tumor of the prostate have previously been reported in the literature. 1–5 Phyllodes tumor of the prostate is histologically classified into benign, borderline and malignant catagories. 1 Benign phyllodes tumors show proliferating cellular stroma, with a low of zero mitotic rate and occasional cellular atypia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐six cases of phyllodes tumor of the prostate have previously been reported in the literature. 1–5 Phyllodes tumor of the prostate is histologically classified into benign, borderline and malignant catagories. 1 Benign phyllodes tumors show proliferating cellular stroma, with a low of zero mitotic rate and occasional cellular atypia.…”
Section: Discussionmentioning
confidence: 99%
“…Borderline cases histologically have features of intermediate characteristics of both types. As four cases of borderline types previously reported were followed up with a clinical course for the malignant category, 1,2,6,7 health professionals should be careful in following up the borderline cases. Young et al suggested that stromal mitotic activity may be a useful prognostic feature for phyllodes tumor of the prostate, 7 but in the case discussed by Yamada et al the patient had rare mitosis and died of a recurrent tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se presentan frecuentemente con síntomas del tracto urinario bajo, hematuria, hematospermia o masa al examen rectal [1][2][3] . Poseen características típicas pero no ú nicas en los estudios de imagen 4 . El tratamiento adecuado es la exéresis quirú rgica del tumor.…”
Section: Sr Directorunclassified
“…When tested by immunohistochemistry the prostatic stromal cells are positive for androgen and progesterone receptors but not for estrogen receptors. [1][2][3] Many authors described lesions arising from the specialized prostatic stroma under several designations, including atypical stromal hyperplasia, 4,5 atypical stromal smooth muscle hyperplasia, 6 atypical fibromuscular hyperplasia, 7 phyllodes type of hyperplasia, [8][9][10][11][12] phyllodes tumor, 7,12-17 cystadeno-leiomyofibroma, 18 prostatic cystic epithelial stromal tumor, 19 cystosarcoma phyllodes, [20][21][22][23][24][25][26] pseudosarcomatous lesions of the prostate, 27 malignant phyllodes tumor of the prostate, 14,15,22,23,28,29 and stromal sarcoma of the prostate. 30 Gaudin and colleagues reported their experience with 22 tumors of the specialized prostatic stroma and proposed a unifying concept under which many of the previously described entities could be included.…”
Section: Lesions Of the Specialized Prostatic Stromamentioning
confidence: 99%